ANALISIS IMPLEMENTASI DIMENSI BUDAYA KESELAMATAN PASIEN OLEH PETUGAS KESEHATAN DI PUSKESMAS WILAYAH KERJA DINAS KESEHATAN KABUPATEN KARANGASEM - Indrayathi, Putu Ayu; Krismayanti, Ni Kadek Ari (ARCHIVE OF COMMUNITY HEALTH, 2024)
Patient safety is a system that makes patients safer. One of the factors in the success of patient safety programs is from the culture. This research aims at investigating the implementation of patient safety culture dimension by health workers in Primary Health Care (Puskesmas) Karangasem Regency. It was designed in descriptive qualitative methods. The informants of this study were health workers in the Kubu I Puskesmas, Selat Puskesmas, and Karangasem Regency Public Health Office which were totally 17 people using the purposive sampling technique. The instrument used for gathering data was using in-depth interview guides. Data analysis was carried out through transcribing interviews, coding, open coding, looking for patterns and relationships, drawing conclusions and interpreting data. The results showed that the implementation of patient safety culture in Primary Health Care was unclear and firm. Implementation of Primary Health Care with the highest and lowest visits did not have a significant difference. Significant differences in the number of incidents between Primary Health Care occur due to low recording awareness. The obstacles encountered in implementing a patient safety culture were overlapping, lack of training and guidelines related to patient safety. The conclusion of this study is the implementation of a culture of patient safety in Primary Health Care is not optimal and needs to be improved. Support is needed from all aspects both from the health department and from the Primary Health Care to be able to create patient safety at the Primary Heath Care. Keywords : Patients Safety, Health Workers, Primary Health Care